PENERAPAN IPTEKS KELOMPOK WIRAUSAHA MANDIRI DI DESA PEMARON, KABUPATEN BULELENG DALAM MEMBUAT OLAHAN SIRUP STROBERI DAN PEMILIHAN KEMASAN PRODUK - Julyasih, Ketut Srie Marhaeni; Pertiwi, Ni Putu Dian (Universitas Mataram, 2024)
Increasing the skills of the group of entrepreneurial mothers at the Pemaron Asri Housing Complex, Pemaron Village, Buleleng Regency, Bali Province was carried out through a science and technology implementation program. This activity is focused on improving the skills of mothers who are just starting a home business, but are hampered in the areas of knowledge and skills in making local processed fruit products that are available, but not yet widely used by the community. The training on diversification of processed strawberries aims to improve the skills of entrepreneurial mothers in making a variety of processed products from strawberries. Through the method of carrying out activities, namely the lecture method (presentation) and practice in making diversified strawberry syrup, it is hoped that it can provide added value (added value) to strawberries both in terms of type variants, taste, nutrition and packaging methods for strawberry syrup. This training places more emphasis on participant responsibility and is able to provide ongoing training and assistance in managing business activities for processed strawberry products. The results of activities from the science and technology application program in Pemaron village targeting the group of entrepreneurial mothers were an increase in the skills of group members in processing strawberries into strawberry syrup products. Apart from that, their knowledge regarding techniques for making strawberry syrup also deepens regarding the correct processing process and their skills in determining product packaging designs that attract the target market.